THE EXAMINATION OF THE STRATEGIES AND SOLUTIONS TO THE PROBLEM OF UNEMPLOYMENT - Kumar Garg, Parveen; Sethi, Ashwani (International Journal of Psychosocial Rehabilitation, 2021)
Investments in training and education are one of the most important things that can help people acquire the required skills and knowledge for employment. However, in this changing environment, with a lot of emerging technologies, the major challenges facing many people are keeping up with the needed market skills and investing in upskills. This paper presents a comprehensive literature review using a content analysis approach to investigate the reasons for the unemployment problem across many countries and identifies proposed solutions and suggestions to handle this problem, particularly the problem of skills mismatch. The results indicated that the previous solutions were inadequate as they used reactive strategies; thus, people cannot respond quickly to change in the market and acquire the required skills immediately.